Next Generation Marine Wireless Communication Networks - Lin, Bin.; Duan, Jianli; Han, Mengqi; Cai, Lin X.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents a novel framework design for the next generation Marine Wireless Communication Networks (MWCNs). The authors first provide an overview of MWCNs, followed by a discussion of challenges in the design and development of MWCNs in support of a diversity of marine services such as real-time marine monitoring, offshore oil exploration, drilling, marine tourism and fishing. The authors then propose cross layer networking solutions to achieve a high performance modern MWCN that enables efficient and reliable data transmissions under hostile marine environment, which include the network deployment, the physical layer channel coding, intelligent network access and resource management, and learning-based opportunistic routing. Finally, the authors summarize the book and present some open issues that will lead to new research directions in the next generation MWCNs. Presents a comprehensive survey on existing marine wireless communication networks (MWCNs) and marine applications; Provides a thorough review of key technologies and their potential development prospects in MWCNs; Proposes networking solutions for high performance MWCNs, namely optimal topology management, the physical layer channel coding, intelligent network access and resource management, and learning-based opportunistic routing.
Introduction -- Overview of Marine Wireless Communication Networks (MWCNs) -- Topology Optimization of Marine Wireless Networks -- Autoencoder with Channel Estimation for Marine Communications -- Enabling Sustainable Underwater IoT Networks with Energy Harvesting -- Learning based Opportunistic Routing for Marine Wireless Sensor Networks -- Future research directions -- Conclusion.
Keywords: Telecommunication; Underwater acoustics; Oceanography; Communications Engineering, Networks; Microwaves, RF Engineering and Optical Communications; Underwater Acoustics; Ocean Sciences; Wireless communication systems; Marine engineering